2018
DOI: 10.3390/cancers10100348
|View full text |Cite
|
Sign up to set email alerts
|

Role of COX-2/PGE2 Mediated Inflammation in Oral Squamous Cell Carcinoma

Abstract: A significant amount of research indicates that the cyclooxygenase/prostaglandin E2 (PGE2) pathway of inflammation contributes to the development and progression of a variety of cancers, including squamous cell carcinoma of the oral cavity and oropharynx (OSCC). Although there have been promising results from studies examining the utility of anti-inflammatory drugs in the treatment of OSCC, this strategy has been met with only variable success and these drugs are also associated with toxicities that make them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
92
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(96 citation statements)
references
References 179 publications
(197 reference statements)
4
92
0
Order By: Relevance
“…Numerous epidemiological studies have shown that the regular intake of the NSAID aspirin, an inhibitor of COXs, substantially reduces both the incidence and progression of several prevalent cancers [20]. Abundant epidemiological and preclinical/clinical studies have demonstrated that celecoxib, a specific COX-2 inhibitor, is related to the suppression of cancer cell proliferation and a decrease in cancer incidence [21]. COX-1 is constitutively expressed in many tissues and regulates basal levels of prostaglandins [22].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous epidemiological studies have shown that the regular intake of the NSAID aspirin, an inhibitor of COXs, substantially reduces both the incidence and progression of several prevalent cancers [20]. Abundant epidemiological and preclinical/clinical studies have demonstrated that celecoxib, a specific COX-2 inhibitor, is related to the suppression of cancer cell proliferation and a decrease in cancer incidence [21]. COX-1 is constitutively expressed in many tissues and regulates basal levels of prostaglandins [22].…”
Section: Discussionmentioning
confidence: 99%
“…reported that cetuximab could suppress the proliferation of cancer cells by inhibiting COX-2/PGE2/EGFR pathway [23]. But the molecular mechanism of β2-AR regulates the expression of EGFR has not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…Cyclooxygenase-2 (COX-2) is overexpressed and closely related the poor prognosis and progression of malignant tumor, including OSCC [18][19][20][21]. Just like β2-AR, COX-2 is closely related to proliferation, apoptosis, angiogenesis, invasion, metastasis and immunosuppression of OSCC [22,23]. Different studies reported that COX-2 inhibitor could signi cantly inhibit progression of OSCC [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes with high concentrations of prostaglandins transport more PGE2 to neighboring cells, enhancing the overall presence of PGE2 in the microenvironment (Subra et al 2010). Cell motility and metastatic status are impacted by extracellular levels of PGE2 (Nasry et al 2018). Evidence has shown that exosomes rich in PGE2 participate in tumor immune evasion and promote tumor growth (Record et al 2014).…”
Section: Lipid Cargo In Oscc Exosomesmentioning
confidence: 99%